Systems Medicine as an Emerging Tool for Cardiovascular Genetics - Haase, Tina; Börnigen, Daniela; Müller, Christian; Zeller, Tanja (Frontiers in Cardiovascular Medicine, 2016)
Cardiovascular disease is a major contributor to morbidity and mortality worldwide. However, the pathogenesis of cardiovascular disease is complex and remains elusive. Within the last years, systems medicine has emerged as a novel tool to study the complex genetic, molecular and physiological interactions leading to diseases. In this review, we provide an overview about the current approaches for systems medicine in cardiovascular disease. They include bioinformatical as well as experimental tools such as cell and animal models, omics technologies, network and pathway analyses. Additionally, we discuss challenges and current literature examples where systems medicine has been successfully applied for the study of cardiovascular disease.